Immunogystochemical (Sd-138 Marker) Results Of Pathomorphological Changes In The Uterus When Drinking Energy Drinks Chronically Under Experimental Conditions - Ishankulova Dildora Khabibullaevna (Zien Journals, 2024)
In this study, the experimental method examined the morphological changes that occur in uterine tissue and glands when white non-breeding rats are ingested in chronic energy drinks in an immunogystochemical manner. From micropreparations made from uterine tissue structures isolated from white non-breeding bats, immunogystochemical testing was performed using the CD-138 marker to produce data on the results obtained based on the degree of expression of the same marker
Keywords: CD-138 marker; plasmatic cells; immunogystochemistry; chronic endometritis